Evaluation of rice cultivars for resistance to rice yellow mottle virus - Kam, H.; Ndjiondjop, M.N.; Ouédraogo, N.; Laing, M.D.; Ghesquière, Alain (African Journals Online, 2018)
Rice yellow mottle virus (RYMV), which is only found in Africa, threatens rice farming on the continent. A local Oryza sativa cultivar collected from Burkina Faso (named BM24), was evaluated with that of well known highly resistant and tolerant cultivars. Firstly, three RYMV isolates were used to characterise the differential interaction within the cultivars. Secondly, disease kinetics of symptom expression and virus titer on leaves at 21 days after inoculation were assessed using the BF1 isolate. Thirdly, the allelic profile of O. sativa varieties using SSR marker RM101 located on chromosome 12 was also assessed. IR64 showed susceptibility to all isolates; while Tog5681 was resistant to all isolates. Ng122 overcame the resistance of Gigante, with mild leaf symptoms at 42 dpi. Azucena and BM24 had, therefore, different resistance level regarding the three isolates (Ng117b, Ng122 and Ng144). When infected with the isolate, BF1, BM24 and Azucena exhibited same resistance patterns in early growth stages with delayed of symptoms appearance, but BM24 outperformed Azucena at later stages. The virus content in the two accessions, at 14 days post inoculation, was statistically different with BM24, showing less virus compared to Azucena. However, the two accessions depicted an identical allelic profile at RM101 locus.